Efektivitas Pemberantasan Tindak Pidana Penimbunan Beras Tidak Standar Sanitasi Pangan Di Wilayah Hukum Polda Bali - I Wayan Agus Arya Juliartha P; A.A. Kt Sudiana (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
Food is one of the primary (primary) needs of humans. Food shortages can occur for various reasons, including natural and human-caused factors. For example, hoarding of food (rice) by unscrupulous traders. The Food Task Force Team of the Bali Regional Police's Special Criminal Investigation Directorate carries out routine activities such as market patrols and inspections of rice storage warehouses to curb hoarding by unscrupulous traders. Article 133 of Law Number 18 of 2012 concerning Food regulates the criminal act of hoarding or storing staple foods by food businesses. This study uses an empirical legal research method, examining the legal behavior of the community because it emphasizes field data and existing problems within the community as research subjects. The conclusion of this study is that the effectiveness of eradicating rice hoarding and violating food sanitation standards in the Bali Regional Police jurisdiction is not yet fully effective. This is due to limited monitoring facilities and infrastructure, the vast food distribution area, and low legal awareness among business actors.